HUKUM ASAL TALAK DALAM ISLAM : KOMPARASI PENDAPAT IBNU TAIMIYAH DAN JUMHUR ULAMA - Raja Asyad Vatanen; Muhamad Arifin (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study examines the foundational ruling of divorce (talak) in Islam through a comparative analysis of the views of Ibn Taymiyyah and the majority of scholars (jumhur). Ibn Taymiyyah argues that the original ruling of talak is prohibited unless there is a legitimate shar’i reason, such as irreparable marital conflict. In contrast, the jumhur scholars maintain that talak is permissible (mubah) as a right granted by Islamic law, though its use must consider benefit and harm (maslahat wa mafsadat).The study explores the evidences supporting both views, sourced from the Qur’an and Hadith, as well as their implications in modern society. Ibn Taymiyyah’s perspective emphasizes protecting marital harmony and discouraging unnecessary divorces. Meanwhile, the jumhur approach provides flexibility, offering solutions for various marital circumstances.In conclusion, these differing opinions reflect the richness of Islamic legal thought while aligning with the overarching objectives of shari’ah: ensuring justice, promoting welfare (maslahat), and safeguarding the institution of marriage. This research highlights the relevance of these perspectives for addressing contemporary challenges in Islamic family law.